Catch bond models may explain how force amplifies TCR signaling and antigen discrimination - Hyun-Kyu Choi; Peiwen Cong; Chenghao Ge; Aswin Natarajan; Baoyu Liu; Yong Zhang; Kaitao Li; Muaz Nik Rushdi; Wei Chen; Jizhong Lou; Michelle Krogsgaard; Cheng Zhu (Nature Communications, 2023)
Abstract The TCR integrates forces in its triggering process upon interaction with pMHC. Force elicits TCR catch-slip bonds with strong pMHCs but slip-only bonds with weak pMHCs. We develop two models and apply them to analyze 55 datasets, demonstrating the models’ ability to quantitatively integrate and classify a broad range of bond behaviors and biological activities. Comparing to a generic two-state model, our models can distinguish class I from class II MHCs and correlate their structural parameters with the TCR/pMHC’s potency to trigger T cell activation. The models are tested by mutagenesis using an MHC and a TCR mutated to alter conformation changes. The extensive comparisons between theory and experiment provide model validation and testable hypothesis regarding specific conformational changes that control bond profiles, thereby suggesting structural mechanisms for the inner workings of the TCR mechanosensing machinery and plausible explanations of why and how force may amplify TCR signaling and antigen discrimination.